ELECTRICAL CHARACTERIZATION OF MEAT OBTAINED FROM PROPERLY AND NON-PROPERLY SLAUGHTERED ANIMALS - MAHFOUDH MOHIRI, ABDULLAH SAEED (2012)
Meat is a biological tissue that supplies the human body with protein necessary for growth. Meat with high blood content, however, is considered as an unhealthy meat because the blood retained in the meat could potentially become a growth medium for hazardous microorganisms and bacteria. To obtain the healthy meat, a proper animal slaughtering process that causes a rapid and thorough bleeding out must be used. More importantly, there is a need to develop a technique that distinguishes meat obtained from properly and non-properly slaughtered animals. This thesis aims to distinguish between properly and non-properly slaughtered goat meat using its electrical properties. In this work, the permittivity of goat meat was predicted, first, using dielectric mixing rules to investigate the effect of blood content on the permittivity dispersion of meat.